2022
DOI: 10.3390/ijerph192215357
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of a Family-Focused, Gender-Transformative Intervention on Adolescent Girls’ Well-Being in a Humanitarian Context

Abstract: While family functioning interventions show promise for improving adolescent girls’ well-being in humanitarian contexts, few programs employ a gender-transformative approach to maximize benefits for adolescent girls. This paper presents findings from a mixed-methods pilot evaluation of a whole-family, gender-transformative intervention conducted with Syrian refugee families in Jordan. The Siblings Support of Adolescent Girls in Emergencies program was implemented with 60 Syrian refugee households in Azraq and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This Special Issue also widens the lens on the ways in which we think about the impacts of IPV on wellbeing. The studies included employ traditional measures of depression, post-traumatic stress disorder, and suicide ideation [ 25 , 26 , 27 , 28 ], but also examine broader psychosocial impacts such as alcohol and drug use, capacity to cope, and resilience [ 18 , 27 , 29 , 30 , 31 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue also widens the lens on the ways in which we think about the impacts of IPV on wellbeing. The studies included employ traditional measures of depression, post-traumatic stress disorder, and suicide ideation [ 25 , 26 , 27 , 28 ], but also examine broader psychosocial impacts such as alcohol and drug use, capacity to cope, and resilience [ 18 , 27 , 29 , 30 , 31 ].…”
mentioning
confidence: 99%
“…For example, while a study from Northern Uganda found that gender equitable attitudes mitigated the relationship between IPV victimization and mental illness [ 29 ], analyses from Nigeria revealed that survivors of IPV who believed IPV was acceptable in some situations exhibited lower mental distress [ 26 ]. Third, this Special Issue offers actionable guidance for practitioners by evaluating promising intervention approaches [ 30 , 34 ], reviewing the evidence on what works to prevent IPV and subsequent psychological distress [ 35 , 36 ], and highlighting determinants for the successful implementation of integrated interventions that address IPV and mental health in tandem [ 37 ]. Importantly, all papers in this Special Issue advance the knowledge base on how to understand and address IPV and mental health in LMICs, ultimately strengthening our ability to make progress toward the SDGs.…”
mentioning
confidence: 99%
“…Qualitative data collected from participants in Nigeria revealed key ways in which the program improved elements of family functioning; participants reported more equitable gender roles and attitudes such as joint decision making among caregivers, men and boys' participation in household labor, reduced stigma when discussing menstruation and puberty and a reduction in intrahousehold violence against girls [30,31]. Additional positive impacts for adolescent girls were demonstrated in Jordan, where girl participants exhibited higher levels of mental well-being, resilience, and perceived family functioning [32]. Although previous implementation experiences highlight positive reflections for participants, this study will assess SSAGE's impact on mental health through the mechanisms outlined in Fig 1 and identify potential barriers to implementation that may circumscribe the program's intended effects.…”
Section: Plos Onementioning
confidence: 99%
“…16 Although reaching adolescents is often challenging in any setting, many commonly used points of access may be inappropriate in humanitarian and fragile settings. For example, school based interventions, while cost effective, do not reach the high proportions of adolescents who are out of school or mobile in such settings; similarly, community based interventions such as safe spaces 17 may fail to reach female adolescents, who often have restricted mobility in public spheres; finally, family based interventions, though promising, 18 may face resistance or time constraints among families affected by conflict, disaster, or forced displacement.…”
Section: Limited and Poor Quality Evaluation Of Interventionsmentioning
confidence: 99%